Sertraline induced urinary retention : A case report - Shakya, R.; Shah, B. (Journal of Psychiatrists' Association of Nepal, 2018)
SSRI is widely used because of its low side effect profile and better tolerability than the older antidepressants. Urinary side effects are uncommon with SSRI as they lack anticholinergic effects. We present a case of young female, who in her postpartum period, developed urinary retention on tab sertraline. Extensive evaluation was done to rule out gynaecological, neurological and urological conditions. She was successfully treated and maintained on tab fluoxetine. Thus, it is suggested that clinicians should be cautioned about potential urinary problems associated with sertraline. Timely detection and management maintains compliance to the medication, helps in recovery from the illness and improves quality of life.